2021
DOI: 10.1038/s41392-021-00774-2
|View full text |Cite
|
Sign up to set email alerts
|

The existence of a nonclassical TCA cycle in the nucleus that wires the metabolic-epigenetic circuitry

Abstract: The scope and variety of the metabolic intermediates from the mitochondrial tricarboxylic acid (TCA) cycle that are engaged in epigenetic regulation of the chromatin function in the nucleus raise an outstanding question about how timely and precise supply/consumption of these metabolites is achieved in the nucleus. We report here the identification of a nonclassical TCA cycle in the nucleus (nTCA cycle). We found that all the TCA cycle-associated enzymes including citrate synthase (CS), aconitase 2 (ACO2), iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 77 publications
2
31
0
Order By: Relevance
“…Furthermore, their study showed that CS can cause hypersensitivity, senescence, and an inability to synthesize citrate, which plays an important role in sperm aging, suggesting possible infertility due to susceptibility(Kang et al, 2020; Rahimizzadeh et al., 2020).Various recent studies have shown that TCA dysfunction (tricarboxylic acids are the main source of cellular energy and are involved in many metabolic processes within cells) causes human diseases such as neuro-metabolic disorders and tumors is shown. These studies therefore demonstrate that CS can use this modified SDHA to control the reductive and oxidative orientation of the TCA cycle(Liu et al, 2021). In addition, metabolomics analysis of aged sperm indicated that loss of CS increased her TCA turnover in mitochondria with age, which could lead to a decrease in extra-mitochondrial citrate.…”
mentioning
confidence: 68%
“…Furthermore, their study showed that CS can cause hypersensitivity, senescence, and an inability to synthesize citrate, which plays an important role in sperm aging, suggesting possible infertility due to susceptibility(Kang et al, 2020; Rahimizzadeh et al., 2020).Various recent studies have shown that TCA dysfunction (tricarboxylic acids are the main source of cellular energy and are involved in many metabolic processes within cells) causes human diseases such as neuro-metabolic disorders and tumors is shown. These studies therefore demonstrate that CS can use this modified SDHA to control the reductive and oxidative orientation of the TCA cycle(Liu et al, 2021). In addition, metabolomics analysis of aged sperm indicated that loss of CS increased her TCA turnover in mitochondria with age, which could lead to a decrease in extra-mitochondrial citrate.…”
mentioning
confidence: 68%
“…Compartmentalized acyl-CoA metabolism is important for chromatin regulation (Trefely et al, 2020). Studies have shown that histone acylations, including acetylation, crotonylation, and succinylation, are regulated by the corresponding acyl-CoA-producing enzymes localized in the nucleus (Liu et al, 2017; Liu et al, 2021; Nagaraj et al, 2017; Sutendra et al, 2014; Wang et al, 2017; Wellen et al, 2009). In the present study, we found that, in addition to the canonical cytoplasmic localization, ACC was present in nucleus, and partly localized in nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…The TCA cycle enzymes in the mitochondria are also present in the nucleus [ 132 ] and are a part of an incomplete cycle that produces metabolic intermediates which control transcription by epigenetic modification. All the TCA mitochondrial enzymes except succinate dehydrogenase are found in the nucleus.…”
Section: Nuclear Kgdhc Alters Transcription (Epigenetic Effect)mentioning
confidence: 99%